The Lagos Neighbourhood Safety Corps and Urban Crime in Lagos Metropolis - Oluwalogbon , Leke Abraham (Kashere Journal of Politics and International Relations, 2024)
This qualitative study explored the impact of the Lagos Neighbourhood Safety Corps (LNSC) on crime reduction in Lagos Metropolis, utilising a community policing approach and collaborations with law enforcement agencies. Seven in-depth Key Informant Interviews were conducted with LNSC officials at the agency's headquarters in Lagos, Nigeria, providing rich insights into the agency's operations, challenges, and strategies. The study revealed that LNSC's community-focused approach has led to a perceived reduction in crime rates, with respondents citing increased security presence and swift response to criminal activities. The agency's collaborative relationships with other law enforcement agencies were also highlighted, demonstrating a unified approach to combating crime. However, the study also identified challenges that hinder LNSC's effectiveness, including inadequate training, public unawareness, and funding constraints. To optimise its performance, the agency needs to enhance public awareness, training, and equipment deployment. The findings emphasise the importance of community-centred approaches to security and the need for sustained support for initiatives like LNSC, critical in maintaining public safety and security in Lagos Metropolis. By addressing the identified challenges, LNSC can enhance its impact and contribute to a safer, more secure Lagos. This study highlights the potential of community policing initiatives in reducing crime and promoting public safety, providing valuable insights for policymakers and law enforcement agencies.